ENSO–Kalahari Desert linkages on southern Africa summer surface air temperature variability. (28th June 2016) - Manatsa, Desmond; Reason, Chris
ABSTRACT: In this work, we use observational and reanalysis data to demonstrate the prominent role which is played by the Kalahari Desert in the modulation of the maximum surface air temperature (SATmax ) over southern Africa during austral summer. It is not only the El Niño Southern Oscillation (ENSO) related modification of the middle and upper troposphere but the coupling to the desert surface through cloud development mechanisms which contribute immensely to the SATmax extremes. This is achieved through the convective cloud enhancement mechanisms linked to the tropical temperate troughs and suppression processes forced by the Botswana Upper High during La Niña and El Niño events, respectively. However, significant ENSO impact on the regional SATmax is restricted to the setting in of the Indian Ocean basin‐wide sea surface temperature (SST) mode in December. This SST mode is unique and specifically characterizes the distinctive nature of the canonical version of the ENSO extremes. In this regard, the prominent anomalous warming and cooling of SATmax is predominantly explained by the canonical El Niño and La Niña events, respectively. On the other hand, ENSO 'modoki' cases appear not only to have notably reduced impacts on SATmax but have effects which are opposite in sign relative to their canonical ENSO counterparts. Therefore, factors which modulate ENSO characteristics, be they natural or anthropogenic, should have strong implications on the environment, water resource availability and societies of southern Africa.